2012
DOI: 10.1002/jsfa.5754
|View full text |Cite
|
Sign up to set email alerts
|

Albusin B modulates lipid metabolism and increases antioxidant defense in broiler chickens by a proteomic approach

Abstract: Albusin B supplementation modulated lipid metabolism and activated systemic antioxidant defense, which might partially contribute to the performance of broiler chickens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Our previous study found that BA supplementation could modulate the lipid metabolism of broiler chickens, and that BA increased endogenous cholesterol synthesis and recruited cholesterol from peripheral tissue to the liver [9]. However, there was no significant difference in serum cholesterol or LDL-C levels between the control and BA+LAB treatment groups.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our previous study found that BA supplementation could modulate the lipid metabolism of broiler chickens, and that BA increased endogenous cholesterol synthesis and recruited cholesterol from peripheral tissue to the liver [9]. However, there was no significant difference in serum cholesterol or LDL-C levels between the control and BA+LAB treatment groups.…”
Section: Discussionmentioning
confidence: 96%
“…There is increasing evidence that probiotics and their cell components modulate the metabolic process of the host, including lipid metabolism [26]. Our previous study on BA supplementation also indicated that the BA modulated the lipid metabolism and resulted in the lower TG levels of broiler chickens [9]. Compared to the control group, the broiler chickens fed with YC showed no effect on TG levels, suggesting that the BA supplementation effect on TG levels was not caused by the yeast host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creatine kinase, an enzyme catalyzing the reversible phosphorylation of creatine for cellular maintenance and energy transport [4], decreased over time in the challenged birds; it was also found to be reduced in the intestinal proteome in albusin B supplemented broilers [4]. Cytochrome b-c1, α-enolase and NADPH cytochrome p450 reductase, all enzymes in molecular pathways associated with energy metabolism, such as glycolysis, the electron transport chain and ATP synthesis all decreased in abundance over time in the challenged birds.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocins, a heterogeneous group of proteinaceous compounds lethal to bacteria other than the producing strain, were found to cause differential abundance of metabolic-related proteins within the jejuna, many of which were antioxidants [4]. The feeding of the probiotic Enterococcus faecium ( E. faecium ) , resulted in the differential abundance of 42 intestinal mucosal proteins, including those related to intestinal structure and immune and antioxidant systems of which 6 were abundant in the broilers fed E. faecium [5].…”
Section: Introductionmentioning
confidence: 99%